Complete Whole-Genome Sequence of Streptomyces sp. MUM 178J, a Potential Anti-Vibrio Agent - Ke-Yan Loo; Loh Teng-Hern Tan; Kah-Ooi Chua; Priyia Pusparajah; Kok-Gan Chan; Learn-Han Lee; Jodi Woan-Fei Law; Vengadesh Letchumanan (Progress in Microbes and Molecular Biology)
Streptomyces sp. is a group of filamentous, Gram-positive bacteria notoriously known for their capabilities in producing bioactive compounds that have been used as novel drugs and lead in drug development. The Streptomyces sp. MUM 178J was isolated from a mangrove forest in Malaysia. This isolate was found to harbor anti-Vibrio properties as its crude extract inhibited the growth of multidrug-resistant Vibrio parahaemolyticus. Therefore, the strain was subjected to whole genome sequencing to unearth its genomic potential. The genome of Streptomyces sp. MUM 178J consists of 6,699,249 bp with a G+C content of 71.3%. 66 tRNA genes and 18 rRNA genes were also predicted to be present within the genome. Further analysis with the bioinformatics tool, antiSMASH (antibiotics & Secondary Metabolite Analysis Shell), detected nine biosynthetic gene clusters displaying more than 70% similarity to known gene clusters, including one associated with melanin production. Melanin has demonstrated antagonistic activity against the growth of members of the Vibrio family, including V. parahaemolyticus. This indicates the potential correlation between the production of melanin and the anti-Vibrio properties of MUM 178J. The availability of the whole genome sequence of Streptomyces sp. MUM 178J allows for future in-depth investigation and potential exploitation of MUM 178J to harvest useful bioactive compounds.